Current Status of COX-2 Inhibitors - Singh, Palwinder; Mittal, Anu (Mini Reviews in Medicinal Chemistry, 2008)
The two isoforms of enzyme cyclooxygenase viz. COX-1 and COX-2 play key roles in the metabolism of arachidonic acid. The enzyme COX-2, when over expressed, leads to more production of prostaglandins causing inflammation and it also participates in the propagation of cancer. Therefore, COX-2 becomes the cellular target of a number of chemical entities for the treatment of inflammatory diseases as well as for the chemotherapy of cancer. In the present review, an up to date status of the compounds investigated for COX-2 inhibition has been given so that a collective view of the existing COX-2 inhibitors could be helpful for the design of safer anti-inflammatory drugs. In order to cover the maximum reported COX-2 inhibitors, a unique classification on the basis of the central core of the molecule (carrying mostly the phenyl moieties) has been followed, an outline of which has been given below: Each category of compounds has been discussed with suitable examples giving the IC50 (for COX-2) values and the selectivity towards COX-2 over COX-1 of most potent compounds. Each category of compounds has been discussed with suitable examples giving the IC50 (for COX-2) values and the selectivity towards COX-2 over COX-1 of most potent compounds.
Keywords: carbocyclic and acyclic template